The Contribution of Geography Learning to Disaster Preparedness of Students in Public Senior High Schools in Kendari - Akbar, Ismail; Maryani, Enok; Ningrum, Epon (Indonesia University of Education, 2021)
This research aims to see how to learn geography, how students' disaster preparedness are, and how the contribution of geography learning to disaster preparedness of students in Public Senior High School in Kendari. By using quantitative approach, the data were collected through observation and questionnaires in 5 schools in Kendari which were distributed to 150 students and 10 teachers. The results of students' learning geography with several indicators are presented as follows; with learning variable, 12.5% is categorized as low, 46.5% moderate, 41% high; with preparedness variable, 25.5% is categorized as low, 49.5% medium, 25% high. There is a contribution of geography learning to disaster preparedness with the coefficient of determination R square (R2) of 39.4% while 60.6% is from other factors. Then, the influence of X on Y can be written in the form of a regression equation, namely (Y = 55.998 + 0.159 X). Based on the regression equation, it can be denied that geography learning has a positive correlation with disaster preparedness of students in Public Senior High School in Kendari